An open-label study evaluating the safety and efficacy of AMO-01 for the treatment of seizures in Phelan-McDermid syndrome - Tess Levy; J. Lloyd Holder, Jr.; Joseph P. Horrigan; Michael F. Snape; Alison McMorn; Christina Layton; Hailey Silver; Kate Friedman; Hannah Grosman; Slayton Underwood; Danielle Halpern; Jessica Zweifach; et al. (HGG Advances)
Summary: Phelan-McDermid syndrome (PMS) is a neurodevelopmental disorder caused by haploinsufficiency of the SHANK3 gene. Approximately 25% of individuals with PMS have epilepsy. Treatment of epilepsy in PMS may require multiple anticonvulsants, and in a minority of cases, seizures remain poorly controlled. Converging lines of evidence in different experimental models indicate that the Ras-ERK pathway is implicated in the pathophysiology of seizure generation and neurobehavioral symptoms in PMS. The goal of this study was to evaluate the safety, tolerability, and efficacy in treating seizures in adults and adolescents with PMS using AMO-01, a Ras-ERK pathway inhibitor. A single 6-hour intravenous infusion of AMO-01 at 120 mg/m2 was administered to six participants using an open-label design. Safety was assessed during the infusion and for 4 weeks post-infusion. Caregivers completed seizure diaries and recorded individual seizures during a baseline period and for 4 weeks following the infusion. Exploratory clinical and biomarker assessments were completed throughout the study. AMO-01 was well tolerated, with no serious adverse events (AEs) reported. All AEs were mild or moderate in severity. Seizures were reduced by at least 25% compared to baseline at each follow-up (weeks 1, 2, and 4). Exploratory clinical measures did not change significantly from baseline, but visual evoked potentials (VEPs) and phosphorylated ERK blood levels revealed trending changes in a subset of participants. These results provide preliminary support for the safety of AMO-01 and its efficacy in reducing seizures in adults with PMS. Future placebo-controlled studies with larger sample sizes and repeated dosing are warranted.